Qualitative and quantitative analyses of chemical constituents in vitro and in vivo and systematic evaluation of the pharmacological effects of Tibetan medicine Zhixue Zhentong capsules - Song, Yinglian; Liang, Yan; Zeng, Rong; Li, Ran; Zhou, You; Huang, Sheng; Li, Xiaoli; Zhang, Ning; Xu, Min; Xiong, Kaipeng; Fu, Ke; Ye, Huixuan; et al. (Frontiers in Pharmacology, 2023)
Purpose: This study aimed to profile the overall metabolites of ZXZTC and those entering the blood. Moreover, the contents of six metabolites were measured and the haemostatic, analgesic, and anti-inflammatory effects of ZXZTC were explored. Methods: Ultra-performance liquid chromatography–tandem quadrupole time-of-flight high-resolution mass spectrometry (UPLC-Q-TOF-MS) was employed for qualitative analysis of the metabolites of ZXZTC and those entering the blood. Six metabolites of ZXZTC were quantitatively determined via high-performance liquid chromatography (HPLC). The haemostatic, analgesic, and anti-inflammatory effects of ZXZTC were evaluated in various animal models. Results: A total of 36 metabolites of ZXZTC were identified, including 13 iridoid glycosides, 9 flavonoids, 9 phenylethanol glycosides, 4 phenylpropanoids, and 1 other metabolite. Overall, 11 metabolites of ZXZTC entered the blood of normal rats. Quantitative analysis of the six main metabolites, specifically, shanzhiside methyl ester, chlorogenic acid, 8-O-acetyl shanzhiside methyl ester, forsythin B, luteoloside, and verbascoside were extensively performed. ZXZTC exerted haemostatic effects by reducing platelet aggregation and thrombosis and shortening bleeding time. ZXZTC also clearly had an analgesic effect, as observed through prolongation of latency of writhing, reduction in the number of writhing, and increase in pain threshold of experimental rats. Additionally, significant anti-inflammatory effects of ZXZTC was observed, including reduction of capillary permeability, inhibition of foot swelling, and reduction of proliferation of granulation tissue. Conclusions: Speculative identification of the overall metabolite of ZXZTC and those entering the blood can provide a foundation for determining its biologically active constituents. The established method is simple and reproducible and can help improve the quality control level of ZXZTC as a medicinal product. Evaluating the haemostatic, analgesic, and anti-inflammatory activities of ZXZTC can help study its mechanism.